A reproducible method for extraction of Plasmodium falciparum DNA by microwave irradiation and its potential for rapid molecular diagnosis - Jaturas, N.; Onnoi, N.; Kumar, T.; Jie, B.M.G.; Onichandran, S.; Ponnampalavanar, S.; Thanwisai, A.; Tan, T.C.; Sawangjaroen, N.; Nissapatorn, V. (Malaysian Society of Parasitology and Tropical Medicine, 2015)
Malaria remains one of the most important communicable diseases. A rapid, simple and accurate method is a crucial part of malaria diagnosis. The aim of this study was to re-evaluate the microwave irradiation method to extract DNA from Plasmodium falciparum and compare with six other existing DNA extraction methods such as QIAamp DNA mini kit (Qiagen), FTA elute card, phenol-chloroform, Chelex, Chelex without proteinase-K and Rapid boiling. Two different P. falciparum isolates were used: (i) Laboratory strains with 0.3% parasitemia and (ii) clinical isolate with 0.6% parasitemia. Each DNA extraction method was validated for the presence of P. falciparum by a routine nested and real time PCR. In order to evaluate the sensitivity of the DNA extraction by microwave, double serial dilution of P. falciparum from in vitro culture at parasitemia that ranged from 0.0001 to 0.17% were used to extract the DNA by microwave and the P. falciparum DNA was then detected by nested and real-time PCR. The nested and real-time PCR were able to detect. P. falciparum DNA at the parasitemia level as low as 0.0003% and 0.0001%, respectively. Our results can reproduce the results from earlier studies and reveal microwave as a rapid and simple tool to extract P. falciparum DNA and subsequent molecular diagnosis of malaria.